The Initial Purging Policies after the 1965 Incident at Lubang Buaya - Yosef Djakababa (Journal of Current Southeast Asian Affairs, 2013)
After the Lubang Buaya incident on 1 October 1965 in which six top Indonesian Army generals and a lieutenant were killed, the Army began to implement a nationwide purging campaign with the assistance of civilian anti-communist groups. Thousands of PKI members, supporters and pro-Sukarno groups/individuals immediately became the target of this purge. For organisational purposes, several purging policies were released and then strictly enforced. The official purging policies that are highlighted in this paper are a series of initial directives that were released within days of the generals’ executions. They do not explicitly translate into orders to kill, but are more of a guideline to help anti-communist officials classify and contain communists and other PKI followers. This article attempts to show how these initial directives evolved and also discusses competing purge policies from non-military sources. The co-existence and overlapping nature of the various directives indicate that a power struggle existed between the anti-communist group led by General Soeharto and the presidium of the Dwikora Cabinet who were loyal to President Soekarno.